Evaluation of Anti-obesity Activity of n-hexane and Methanolic Extracts of Cajanus cajan Linn. Seeds Using Enzymatic Methods - Sharma, Sakshi; Rani, Anjna (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: To evaluate the in vitro anti-obesity activity of Cajanus cajan Linn. seeds. Materials and Methods: Phytochemical screening and in vitro studies on pancreatic lipase and alpha-glucosidase activity were performed using methanolic and n-hexane extracts at doses of 100-500 mcg/mL. Results: Cajanus cajan Linn. seeds extracts possess dose-dependent inhibitory activities, showing good anti-obesity potential. Conclusion: Preliminary studies reveal significant potential for treating obesity and its complications.
Keywords: Obesity; Cajanus cajan; Pancreatic lipase